2011
DOI: 10.1021/om200305r
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Selectivity in Suzuki–Miyaura Coupling of Secondary Alkyl Boranes

Abstract: The Suzuki–Miyaura cross-coupling reaction is an important route to forming carbon–carbon bonds. Suzuki coupling of secondary alkyls containing β-hydrogens is challenging, due in part to a competing and undesired β-hydride elimination. We perform density functional electronic structure calculations on model compounds to study the selectivity of Suzuki coupling of secondary alkyl boranes. Results indicate that the rate and selectivity of the desired reductive elimination are strongly influenced by how the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Calculations have revealed that the hydrogens on the most substituted carbon undergo β-hydride elimination most readily. 22 Upon coordination of the stabilizing carbonyl group, the alkyl chain is rotated in such a way that the β-hydrogens at the most substituted carbons are no longer able to become co-planar, thus preventing β-hydride elimination. 14 Finally, electron-withdrawing groups in the substrate have also been found to inhibit β-hydride elimination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations have revealed that the hydrogens on the most substituted carbon undergo β-hydride elimination most readily. 22 Upon coordination of the stabilizing carbonyl group, the alkyl chain is rotated in such a way that the β-hydrogens at the most substituted carbons are no longer able to become co-planar, thus preventing β-hydride elimination. 14 Finally, electron-withdrawing groups in the substrate have also been found to inhibit β-hydride elimination.…”
Section: Resultsmentioning
confidence: 99%
“…The carbonyl of the amide withdraws electron density from the hydrogens β to the palladium, disfavoring β-hydrogen agostic interactions with the metal, thereby further inhibiting β-hydride elimination. 22 …”
Section: Resultsmentioning
confidence: 99%
“…65,66,67,68,69 Furthermore, in all cases racemic alkyl electrophiles were employed, yet the products are produced in high enantiomeric excess. Recent mechanistic studies have elucidated the operating catalytic cycle (Scheme 6).…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…Prior research has demonstrated that these types of ligands can serve several roles in the prevention of β-hydride elimination. One important advantage is their ability to reduce the necessary agostic interactions between the metal and the neighbouring β-hydrogens [78] in two ways: (1) by acting as an inductively electron withdrawing group, thus reducing the electron density of the β-hydrogens, and (2) by coordinating to the metal centre, which reduces the electron deficiency of the metal. Coordination to the metal centre also has the added benefit of potentially inhibiting syn-β-hydride elimination by restricting the conformation of the organometallic intermediate.…”
Section: Stereoselective Couplings Of Alkyl Boronates With Aryl or Almentioning
confidence: 99%